Pengaruh Kepemilikan Asing, Komisaris Asing, Dan Direksi Asing Terhadap Kinerja Keuangan Perusahaan - zulkarnain, zulkarnain (JIFA (Journal of Islamic Finance and Accounting), 2019)
This study examines the effects of foreign ownership, foreign board membership, and foreign directors on firm financial performance of Indonesian food and beverages listed companies in Indonesia Stock Exchange for the periods of 2012-2016. Firm financial performance is measured by ROA. This study employs publicly available data from financial database of a sample of 41 firm observations. Using multiplied analysis linear regression with hypotheses testing of t statistics and F tests, this study finds that foreign directors, partially, had significant positive impact on ROA. The foreign ownership and foreign board membership on the other hand, partially, had no effect on ROA. The foreign ownership, foreign board membership, and foreign directors, simultaneously, had significant positive impact on ROA.Keywords: foreign ownership, foreign board membership, foreign directors, ROA.